Effect Of Compensation On Employee Performance Through Spirit of Work As a Variabel Of Mediation. Case Study in Employees Of Islamic Education Institution. - Fatmah Bagis; Bima Cinintya Pratama; Akhmad Darmawan; Mastur Mujib Ikhsani (ITB AAS INDONESIA Surakarta, 2020)
This study explains about compensation and its effect on employee performance, where the spirit of work is used as a mediation variable. The method used in this study is a case study on the employee of educational institutions in Purwokerto. Questionnaires were administered to 74 employees from the management level to the staff level as respondents. Data analysis techniques used are the analysis of PLS (Partial Least Square) using Smart PLS 3.0. The results showed that Compensation has a significant positive effect on Spirit of work, Spirit of work has a significant positive effect on Employee Performance, Compensation has not a significant effect on Employee Performance and Compensation has a significant effect on Employee Performance through Spirit of work.